The l-component of the unipotent Albanese map - Kim, M; Tamagawa, A (Springer-Verlag, 2008)
We prove a finiteness theorem for the local l ≠ p-component of the Qp -unipotent Albanese map for curves. As an application, we refine the non-abelian Selmer varieties arising in the study of global points and deduce thereby a new proof of Siegel’s theorem for affine curves over Q of genus one with Mordell–Weil rank at most one.